HUBUNGAN TINGKAT KEPUASAN PEMBELAJARAN ONLINE DENGAN PRESTASI AKADEMIK MATA KULIAH NURSING THEORY AND PRACTICE MAHASISWA KEPERAWATAN [RELATIONSHIP BETWEEN ONLINE LEARNING SATISFACTIONAL LEVEL AND NURSING STUDENT ACADEMIC ACHIEVEMENT ON NURSING THEORY AND PRACTICE COURSE] - Cintia K.D.L Telaumbanua; Mario Aditya Pratama Pohus; Zefanya Setya Andika; Yakobus Siswadi; Dwi Yulianto Nugroho (Universitas Pelita Harapan, 2021)
These days, things are developing rapidly, especially in the field of education. One of developments is in the use of technology in education. Online learning is one of important technology-based learning methods in today's world that requires people to do learning activities from home through online learning. The Covid-19 pandemic requires all fields including Education to implement online learning to prevent transmission. The objective of the study was to determine the relationship between online learning satisfaction level on Nursing Theory and Practice course and nursing student academic achievement. This study employed quantitative correlation. The research population is 335 active students Faculty of Nursing Universitas Pelita Harapan batch 2019. Purposive sampling technique and Solvin’s formula were used in this study which involved 185 students. The results show that there is a significant and unidirectional relationship between the level of online learning satisfaction and student learning outcomes (p=0,001). Most students have a level of satisfaction of Nursing Theory and Practice online subjects (68%), with an average learning achievement (final grade) of 81.40. Student satisfaction with online learning methods is related to academic achievement, the higher the level of student learning satisfaction the better students’ academic achievement.BAHASA INDONESIA ABSTRAK: Belakangan ini, banyak hal berkembang dengan pesat, terutama di bidang pendidikan. Salah satu perkembangan tersebut adalah dalam hal penggunaan teknologi dalam pendidikan. Online learning merupakan salah satu metode belajar berbasis teknologi yang penting dalam keadaan dunia sekarang yang mengharuskan kegiatan pembelajaran dilakukan dari rumah melalui pembelajaran online. Pandemi Covid-19 menuntut semua bidang termasuk pendidikan untuk menerapkan pembelajaran online untuk mencegah penularan. Tujuan penelitian ini adalah untuk mengetahui hubungan tingkat kepuasaan pembelajaran online pada mata kuliah Nursing Theory and Practice dengan prestasi akademik mahasiswa keperawatan. Metode penelitian ini menggunakan desain kuantitatif korelasional. Populasi penelitian adalah mahasiswa aktif Fakultas Keperawatan Universitas Pelita Harapan angkatan 2019 berjumlah 335 mahasiswa. Tehnik purposive sampling dan rumus Slovin diterapkan dalam penelitian ini dengan jumlah sampel sebanyak 185 mahasiswa. Hasil dari penelitian menunjukkan adanya hubungan yang signifikan dan searah antara tingkat kepuasan pembelajaran online dengan hasil belajar mahasiswa (p=0,001). Sebagian besar mahasiswa memiliki tingkat kepuasan terhadap pembelajaran Nursing Theory and Practice online (68%), dengan rata-rata prestasi belajar (nilai akhir) 81,40. Kepuasan mahasiswa akan metode pembelajaran online berhubungan dengan prestasi akademik, semakin tinggi tingkat kepuasan mahasiswa terhadap pembelajaran menunjukkan semakin baik prestasi akademik yang dicapai mahasiswa.